A representação da violência ao peregrinar pelas ruas: estudo etnográfico com a população em situação de rua em mossoró-rn - Lira, Cindy Damaris Gomes (Universidade Federal Rural do Semi-Árido, 2019)
There are multiple representations of violence in the daily life of the most diverse societies. In general, the phenomenon of violence is negatively linked to force, the material execution of an act or a dictatorial power intentionally injurious. In order to analyze the violence phenomenon it is necessary to immerse itself interdisciplinarily in historical and cultural contexts of each people, understanding how this phenomenon is constituted and represented. In today's social conjuncture, subjective criteria of classification, symbolism, prejudice, and tacit (silent) exclusion have surfaced as representations of violence. What has been perceived is the contribution of this phenomenon to social suffering, as well as to the aggravation of health. Faced with this, groups lined by social vulnerabilities are even more likely to suffer from violence, and equally inclined to practice violent acts as defense mechanisms. One tacit example of a socially vulnerable group is the Population in a Street Situation (PSR), which, in addition to submission to physical violence, is marked by structural violence with the stigma of crime and social deviance. This dissertation aims to analyze the daily life of the person in a street situation in the city of Mossoró-RN, with emphasis on his discourse on violence. It is an ethnographic study in which the subjects of research are people are or have been in a street situation for a time span of at least 6 (six) months. The research sites were the avenues of the city of Mossoró-RN, as well as welfare institutions that house the PSR. Data collection instruments included semi-structured interviews, observation, construction of field diaries and synoptic tables. The information content constructed was systematized and analyzed by Ethnographic Microanalysis. This study met the requirements of research ethics, without generating any burden to the participants
Keywords: Representação de violência; População em situação de rua; Etnografia; Violence representation; Population in street situation; Ethnography; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES